Analisis Efektivitas dan Kontribusi Penerimaan Pajak Hotel dan Pajak Reklame PAD Kota Bogor - Firli Fissilmi Kaaffah; Imam Sundarta; Rahmat Mulyana Dali (Komunitas Dosen Indonesia, 2023)
This study aims to find out whether the realization of hotel taxes and advertisement taxes has been effective and whether these two taxes have a high contribution to the local revenue of Bogor City. This research method uses a qualitative descriptive analysis method. The research data used is secondary data, which consists of target data and realization of hotel tax revenue, advertisement tax, and PAD from 2018 to 2022. Then the data is processed using effectiveness and contribution analysis. The average level of effectiveness during 2018–2022 for hotel taxes is 121.28%, and 111.42% of advertisement taxes are considered effective. This shows that the Bogor City government has succeeded in achieving the targets of these two taxes. The average contribution rate for hotel tax is 7.89%, and hotel tax is 1.08%, which means that the proportion of hotel tax and advertisement tax makes a small or very small contribution to Bogor City's PAD revenue.